A PHILOSOPHICAL AND HISTORICAL ANALYSIS OF WILLIAM LANE CRAIG'S RESURRECTION OF JESUS ARGUMENT. Issue 39 (12th December 2014) - Lataster, Raphael
<x content-type="archive" xml:space="preserve">Abstract</x> William Lane Craig is a prolific Christian apologist who has written many articles and popular books on the mainly philosophical arguments for God's existence, and is famed for his debating, and his engaging with the public. His work with philosophical arguments is significant, as there is no confirmed empirical evidence for the existence of God, nor can there be any good historical evidence; sound historical methodology necessarily being dismissive of supernatural claims. Craig has formulated a number of arguments that he presents in a clear and accessible cumulative case.